GROWTH AND YIELD PERFORMANCE OF RADISH AS AFFECTED BY DIFFERENT AMOUNT OF EM-BOKASHI IN LAHAR SOIL - Ronel S. De Guzman; Jamil R. Dagupan (European Journal of Agricultural and Rural Education, 2022)
The study aimed to evaluate the effects of the different amount of EM-bokashi in the performance of radish (Raphanus sativus) planted in potted lahar soil in an open field. It specifically evaluated the effects of EM-bokashi on the growth and yield parameters of radish. It consisted of four treatments and three replications in a Randomized Complete Block Design (RCBD). The treatments were the following: Treatment 1 (no application), Treatment 2 (100g), Treatment 3 (200 g), and Treatment 4 (300g) per pot measuring 10x10x17 inches. Based on the result of the study, Treatment 4 showed a significant difference among the treatments in terms of the average tuber diameter. Also, it showed a highly significant difference in the average number of days to germination, final length of the longest leaf, average tuber length, and average tuber weight. It is further supported by LSD as it showed significant differences in control and among other treatments. Therefore, the application of 300g of EM-bokashi is recommended for radish production. Meanwhile, the researchable areas to be addressed, are the evaluation of higher rates of EM-bokashi due to increasing trends in all parameters, conduct of field testing, assessment of residual effect, combination with other organic fertilizers, and continuous utilization in other crops, particularly long-duration crops, to evaluate its effect further